Operações de hedge com instrumentos derivativos e sua associação à redução da volatilidade dos resultados e à criação de valor: um estudo aplicado às empresas brasileiras não-financeiras - Savegnago, Rogério de Paiva (2017)
This work had the main motivation to verify whether the use of derivative transactions for hedging purposes would be associated with the reduction of earnings volatility and value creation in non-financial Brazilian companies. For that matter, 223 non-financial firms listed on the Brazilian BM&FBovespa stock exchange were surveyed, representing 96.5% of the total market and 85.8% of the quantity of these companies traded in the exchange for the year of 2015, when a profound economic crisis has taken place in this country. As this is a quantitative study based on documental sources, they were carried out based on financial and market data provided by Economativa and BM&FBovespa, through Levene’s test of variance homogeneity, to first test the volatility of earnings represented by the standard deviation of the annual return on equity (ROE) for 2015; and also through a linear multiple regression, being this one used to test the association of hedging transactions through derivatives with value creation of the surveyed companies. The results presented herein demonstrated that companies who hedged their risks in 2015 had volatility in its ROE of 91.39% while the companies who did not hedge in this period had volatility in its returns of 158.02%. Nevertheless, such results were not statistically significant at the level of significance of 5%. The multiple linear regression was performed considering how the quantitative dependent variable value (simplified Tobin's Q) behaved in relation to the independent variable (hedging in 2015) and in relation to control variables as Governance, Size, Profitability and Leverage. In this calculation were also included variables with the multiplicative effect of hedging in conjunction with the control variables size, profitability and leverage. The results from this regression demonstrated that the hedging transactions made in 2015 by the companies herein were negatively associated with value, however such results were not statistically significant. Finally, the results presented herein did not allow the author to infer that non-financial Brazilian companies who used derivative instruments for hedging purposes in its activities in 2015 (a year of a serious economic crisis) significantly incurred in lower volatility in their return on equity nor that such transactions were associated with value creation in the surveyed companies